2015
DOI: 10.1089/apc.2014.0265
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Chronic Obstructive Pulmonary Disease (COPD) in an Urban HIV Clinic: A Pilot Study

Abstract: Increased smoking and a detrimental response to tobacco smoke in the lungs of HIV/AIDS patients result in an increased risk for COPD. We aimed to determine the predictive value of a COPD screening strategy validated in the general population and to identify HIV-related factors associated with decreased lung function. Subjects at least 35 years of age at an HIV clinic in New York City completed a COPD screening questionnaire and peak flow measurement. Those with abnormal results and a random one-third of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 56 publications
1
31
0
1
Order By: Relevance
“…04) [11]. Since the publication of this result, 5 high quality studies using spirometric criteria have found COPD rates between 6% and 21% in groups of 65 to 400 HIV outpatients representative of patients commonly treated in consultation units in the United-States, Spain, Italy and Nigeria [12,13,16,19,20]. Differences in prevalence were expected due to dissimilarities of methodology, age, smoking, histories and country-related respiratory exposure usually observed between the countries, but all of these studies confirmed similar high frequency of COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…04) [11]. Since the publication of this result, 5 high quality studies using spirometric criteria have found COPD rates between 6% and 21% in groups of 65 to 400 HIV outpatients representative of patients commonly treated in consultation units in the United-States, Spain, Italy and Nigeria [12,13,16,19,20]. Differences in prevalence were expected due to dissimilarities of methodology, age, smoking, histories and country-related respiratory exposure usually observed between the countries, but all of these studies confirmed similar high frequency of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of CD4 T-cell count in the pathogenesis of OLD as been suggested in the literature [10,11,36,37]. In two recent studies, Drummond and Shirley have shown an accelerated decline of respiratory function (forced expiratory volume in one second (FEV1) and forced vital capacity (FVC)) in HIV-infected people with lower CD4 cell counts [18,20]. In his cohort of 303 HIV-infected patients, Drummond observed, contrary to our results, that this association with CD4 cell count disappeared after adjustment for HIV viral load suggesting that HIV viral load was more determinant in respiratory decline than CD4 cell level [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tools validated in the general population, such as the COPD-Population Screener (PS) Questionnaire screening questionnaire (13), have low sensitivity (20%) and specificity (79%) when applied to an HIV population (20), underscoring the need for an HIV-specific COPD screening tool. Our tool includes factors common to the validated tools available for COPD screening in the general population and was streamlined to improve efficiency in a busy clinic providing longitudinal HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this lack of detection is due to poor physician awareness is not clear, but one barrier may be that screening often requires referral and evaluation elsewhere (108). The use of readily-available screening tools like peak flow, with or without symptom questionnaires, may be an approach that identifies those who need spirometry (109), but there remains a lack of prospective trials to guide an evidence-based approach to COPD screening in the HIV clinic.…”
Section: Screening For Lung Disease In Hivmentioning
confidence: 99%